Genetic diversity and relationship of domestic Bactrian camels (Camelus bactrianus) in China and Mongolia - Han Jianlin; Ochieng, J.W.; Lkhagva, B.; Hanotte, Olivier H. (2004)
The number of domestic Bactrian camels has been decreasing rapidly in recent years in Central Asia, whereas very little is known about their genetic diversity and relationship. Most of these animals are found today in China and Mongolia. Here, we used 12 microsatellite DNA markers to characterise 140 domestic Bactrian camels from 4 populations of China (n = 84) and 2 populations of Mongolia (n = 56). Genetic diversity, expressed as mean number of alleles and expected heterozygosity (He), were similar in all populations. Genetic distances (DS and DA) indicate closer genetic relationships between populations within each country than between the Chinese and Mongolian populations. Significant differentiation indices (Fst) were obtained for all between-country comparisons (P < 0.01). However, within countries the Fst value between the two Mongolian populations and between four of the six pair-wise comparisons between Chinese populations were not significant (P > 0.05). The lack of genetic differentiation among the Chinese populations is possibly a historical legacy of trading along the Silk Road which favoured gene flow between populations. For Mongolia, it is possibly the result of interbreeding between populations following transhumance. Our results indicate that the domestic Bactrian camels from China and Mongolia should be considered as distinct populations in conservation and breeding programs.